Pengaruh Metode Pembelajaran Project Based Learning Berbasis Pendekatan Lingkungan Untuk Meningkatkan Hasil Belajar IPS Siswa Kelas IV SD Negeri 06 Danger Tahun ajaran 2020/2021 - Meri Yuliani; Muhamad Ridwan Habibi (Peneliti.net, 2021)
The purpose of this study was to improve social studies learning outcomes for fourth grade students at SD Negeri 06 Danger. This research is a quasi-experimental type of research. Research sample are students of class IV A as the experimental class and students of class IV B as a control class. The data collection method used in this study are pretest and posttest assessments. While the data analysis using the technique quantitative approach that serves to test the effect of using the method project based learning on social studies learning outcomes for fourth grade students at SD Negeri 06 Danger. The results of the final test given after students received learning treatment with the lecture method in the control class, obtained an average value of 73.53, which means an increase compared to the results of the initial test. After learning, the final test was held, the number of students who received the very good predicate were 2 students, 12 students received the good predicate, 14 students received the sufficient predicate, the less and none at all. The highest score on this test is 75 and the lowest is 65. The results of the final test held after learning, the number of students who got very good predicate was 10 students, who got good predicate were 14 students, who got enough predicate were 4 students, who got good predicate the predicate is less and not at all. a final test was held with an average score of 79.55. An increase in the results of this test, because students make a discourse based on knowledge that has been learned from the learning treatment that has been given